Characterization of Extracellular Chitinase from Bacillus cereus SAHA 12.13 and Its Potency as a Biocontrol of Curvularia affinis - Muhammad Asril; Didik Supriyadi (Journal of Multidisciplinary Applied Natural Science, 2024)
Bacillus cereus SAHA 12.13 can produce chitinase, an enzyme that digests chitin in the main compounds of cell walls, mycelia, and spores in pathogenic fungi that cause leaf spots on oil palm plants such as Curvularia affinis. This study aims to determine the properties of the chitinase enzyme B. cereus SAHA 12.13 that can inhibit the growth of C. affinis. Chitinase enzyme production and characterization were measured using the Spindler method. Antagonism test against pathogenic fungi using dual culture method by testing cell culture and enzyme crude extract. This result showed that the isolate produced a high level of specific chitinase activity at 37 °C for 45 h of incubation with 8.45 U mg-1 proteins with a growth rate (k) of 0.25 generation/h, and the generation time was 3.96 h/generation. The optimum chitinase activity was achieved at pH 7.0 and 45 °C and was stable for 3 h with a half-life (t1/2) of 770 min. The crude enzyme and cell culture of strain can inhibit the growth of C. affinis by 36.27±0.043% and 34.25±0.041%, respectively. These characteristics indicate that B. cereus strain SAHA12.13 can be used to inhibit C. affinis, which causes leaf blight of oil palm, under varying pH and temperature conditions.